Il video a 360° nella didattica universitaria Modelli ed esperienze - Ranieri, Maria; Luzzi, Damiana; Cuomo, Stefano (Studi e saggi, 2022)
The volume focuses on the educational use of 360° video at the university to bring teachers closer to the adoption of innovative teaching practices. The use of this technology is gaining momentum, attracting the interest of teachers from different subject areas for the potential of 360 ° video to anticipate experiences, especially in risky contexts. The volume offers an insight into the theoretical and methodological dimensions involved, accompanied by an examination of the technical aspects. A large space is devoted to the results of SEPA360, a faculty development project on 360 ° video, and to the good practices it has generated. The book can be a valuable tool for university teachers, teachers and trainers interested in the training use of immersive technologies.